Amplificadores de potência chaveados com comutação não-dissipativa para aplicações em áudio - Oliveira, Ronaldo Castro de (1995)
This work presents a study of a Switching Power Amplifíer with soft commutation, employing ZVS techniques, for audio appücations. The principies of PWM techniques, the fundamentais of switching amplifiers and a comparison with conventional amplifiers are presented. A complete analytical study is developed to obtain abacus of ffequency and power. These normalized curves are shown to be useful in simplifying prototype design. Simulation results confirm the validity of the proposed design procedure, showing the soft-commutation on switches and a good frequency response of the switching amplifiers for variable audio ffequency inputs. Finally, the implemented prototype and experimental results obtained in laboratory are presented. In order to make a comparative analysis between switching amplifiers and conventional amplifiers, the graphics of efficiency, gain and phase are also presented. The proposed design procedure and the digital simulations are validated by the experimental work.